Caracterización del perfil clínico y funcional de pacientes con lesión medular en rehabilitación intrahospitalaria - Contreras S., María Soledad; Cerda A., Lorena; Castro L., Ariel (Revista Hospital Clínico Universidad de Chile, 2018)
Spinal cord injury (SCI) is a pathology that generates great personal, family, economic and social impact. There are two main etiologies that are traumatic (T-SCI) and non-traumatic (NTSCI). These patients receive their rehabilitation in specialized hospital services in the acute and sub-acute phase. A retrospective, descriptive, observational study was designed, reviewing the clinical records of patients diagnosed with SCI at discharge, hospitalized in the Physical Medicine and Rehabilitation Service of the Clinical Hospital of the University of Chile. The general profile of admission of patients with SCI was a young men with NT- SCI, with higher education, paid work and incomplete injury (ASIA B, C, D). An improvement was observed for all patients for the severity of the injury, neurological level, motor level, sensory level and functionality. This is the first study conducted nationwide that provides epidemiological data and functional evolution of patients with SCI and are comparable to those found in the international literature.